The roles of libraries and information professionals in Open Educational Resources (OER) initiatives - Bueno-de-la-Fuente, Gema; Robertson, R. John; Boon, Stuart (My University, 2012)
This report contains the findings of a study carried out by the Centre for Academic Practice & Learning Enhancement (CAPLE) and Centre for Educational Technology and Interoperability Standards (CETIS), at the University of Strathclyde. The study focuses on the involvement of the Library as an organizational unit, and of individual librarians and other information science specialists, in open educational resources (OER) initiatives. This research study contributes to the current Open Educational Resources (OER) Programme [http://www.jisc.ac.uk/oer], an initiative by JISC and the HEA whose objective is to promote the creation, dissemination, access and use of OER. This programme represents a firm commitment by UK Higher Education (HE) institutions to the OER movement. The final conclusions of this study indicate that even if the library and/or librarians are well valued by projects where they are already engaged with, the participation of the library is still not widespread, and a significant lack of awareness exists both from OER initiatives with regards to library activities and from the libraries about the resources released by OER initiatives. However, most of the objectives of content-focused OER initiatives are strongly related to library and information science activities and skills and we consider that their involvement would be of great benefit to those projects not yet engaged with them. We found a clear need to promote the role that libraries and librarians can play in OER initiatives, highlighting the expertise and competencies which libraries and librarians can offer. This active promotion is needed to build awareness among stakeholders about libraries and librarians potential contribution to the OER movement, but also, among libraries and librarians about their key role as OER advocates within and out-with their institutions.
http://publications.cetis.ac.uk/2012/492
Keywords: OER; Open Educational Resources; Information Science; Librarians; Libraries